2006
DOI: 10.1002/adsc.200505394
|View full text |Cite
|
Sign up to set email alerts
|

The High Yield Synthesis of Benzaldehydes from Benzylic Alcohols using Homogeneously Catalyzed Aerobic Oxidation in Acetic Acid

Abstract: The kinetics and yields for the formation of benzaldehydes from benzylic alcohols via aerobic oxidation using homogeneous catalysts in acetic acid are reported. For compounds of the type X-C 6 H 4 CH 2 OH where X ¼ H, 4-CH 3 , 4-OCH 3 , 4-Cl, 4-COOH the observed yields were 84, 78, 57, 88 and 52 mol %, respectively. These yields are comparable to those reported for the stoichiometric Co(III)/Br oxidation of these same benzylic alcohols. These results are limited to benzylic alcohols. The high yields are possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 29 publications
(23 reference statements)
1
47
0
Order By: Relevance
“…1; the analysis revealed that no other products were formed. These simple studies confirm Partenheimer's observations that in benzyl alcohol oxidation catalysed by Co (III), benzoic acid production only begins to accelerate when the benzyl alcohol level in the reaction mixture falls below B10% 25 . That a very small amount of benzyl alcohol, present in benzaldehyde, is evidently involved in preventing the oxidation of benzaldehyde to benzoic acid forms the premise for the more detailed studies presented below.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…1; the analysis revealed that no other products were formed. These simple studies confirm Partenheimer's observations that in benzyl alcohol oxidation catalysed by Co (III), benzoic acid production only begins to accelerate when the benzyl alcohol level in the reaction mixture falls below B10% 25 . That a very small amount of benzyl alcohol, present in benzaldehyde, is evidently involved in preventing the oxidation of benzaldehyde to benzoic acid forms the premise for the more detailed studies presented below.…”
Section: Resultssupporting
confidence: 76%
“…The question has been posed previously and it has long been recognized that benzyl alcohol is one of a diverse group of organic molecules that can act as an inhibitor of benzaldehyde oxidation 25 . Investigations on the reactivity and stability of benzaldehyde, under oxidation conditions date back to the late 1920s; McNesby and Heller gave a comprehensive critical review of the early work in 1954 (ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,3] Oxidation of alcohols to their corresponding carbonyl products is one of the fundamental transformations in organic chemistry; [4] benzylic aldehydes, for example, are versatile intermediates for perfumery and other syntheses of fine chemicals. [5] In large-scale applications the replacement of classical methodologies, based on stoichiometric oxidants such as chromates, selenium dioxide or manganese dioxide, by green sources of oxygen (dioxygen, air, H 2 O 2 ) is highly desirable. [6] The price, atomic efficiency and non-toxic by-products of these end oxidants make them attractive candidates for sustainable alcohol oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, side reactions can be suppressed to some extent, as the relative reactivity of a hydrocarbon substrate and that of its partial oxidation products is known to change considerably in the presence of a catalyst. [3] Several transition metal catalyzed autoxidation reactions have been applied to industrial processes, for example, the production of terephthalic acid, used in the production of polyesters, from p-xylene, which is catalyzed by cobalt(II) acetate bromide, with air as oxidant. [4] The cobalt(II) acetate catalyzed oxidation of hydrocarbons with hydrogen peroxide as oxidant, bromide ions as cocatalyst, and acetic acid as solvent has been reported for the partial oxidation of (substituted) toluenes to the corresponding benzaldehydes.…”
Section: Introductionmentioning
confidence: 99%